Insecticidal activity of Pilocarpus spicatus Saint-Hilaire (Rutaceae) essential oil against the crop pest Dysdercus peruvianus (Guérin-Méneville, 1831) and Oncopeltus fasciatus (Dallas, 1852) (Research, Society and Development, 2020)
Studies were carried out to evaluate the insecticidal activity of Pilocarpus spicatus Saint-Hilaire (Rutaceae) essential oil (EO) on the development of the Hemiptera Dysdercus peruvianus (Guérin-Méneville, 1831) and Oncopeltus fasciatus (Dallas, 1852). Gas Chromatography/Mass spectrometry analysis revealed a chemical composition with sabinene (32.27%) and sylvestrene (27.26%) as major constituents. Topical and continuous treatment with the pure EO induced 100% of mortality while serial dilutions of the EO induced different levels of lethality in a dose response manner. Median lethal dose (LD50) and lethal dose 90% (LD90) were determined. Malformations in insects and permanent or supernumerary nymphs were often observed after treatments, and the use of scanning electron microscopy allowed the analysis of morphological changes. The different biological effects of P. spicatus EO point out its potential as a rich source of bioactive molecules to be used as an alternative control method against agricultural pest insects.